Primer on Percutaneous Ablation of Benign Liver Tumors. Issue 3 (2nd October 2018) - Wells, Shane A.; Ziemlewicz, Timothy J.; Lubner, Meghan G.
Abstract : Watch a video presentation of this article Answer questions and earn CME